Path oriented boolean test generation for single stuck-at fault in combinational circuits - Zhang, Xudong (2008)
To produce reliable electronic systems, defect-free components must be available. Automatic test pattern generation systems distinguish defective components from defect-free components by generating input sets that cause the outputs of a component under test to be different if the component is defective than if it is defect-free. As the logic circuits under test get larger, generating tests is becoming harder. Test generation has been proved to be a NP-complete problem.